Big Book Development in Mathematics Lessons Student Learning Outcomes in Class 1 SDN 085138 Langkat - Salsabila, Alika; Novita Br Panjaitan, Brenda; Hafiza, Siti (International Journal of Students Education, 2024)
Learning mathematics is considered a difficult subject. For this reason, in learning mathematics it is necessary to apply learning media that connects learning concepts so that they are closer to students’ lives. Researchers try to use the big book as a learning medium for the lower classes. This research aims to describe the media development process and produce a product and to determine the feasibility of product quality in the form of big book media in mathematics learning in elementary schools. This research is a type of Research and Development (R&D) research with the ADDIE model which consists of five stages. Data collection uses validation and questionnaires. Data analysis techniques were obtained from the validation results of media experts and material experts as well as the results of teacher and student response questionnaires. The research results show a development process consisting of analysis, design, development, implementation, evaluation. The results of this research show that the percentage of media expert validation was 85% and the percentage of material expert validation was 87.5% with very feasible criteria. The results of the teacher questionnaire obtained a percentage of 92.6% and the student questionnaire response was 90.8% with very appropriate criteria. Based on data analysis, it can be concluded that there is product quality in the form of suitability so that the big book media can be used as a mathematics learning media, especially in class 1 of the 085138 Langkat State Elementary School.